Redes sociales virtuales y la bioética (2011)
This piece of research tends to inquire into the (obsessive) psychological, socio-family, physiological, and emotional conditions of the students at Saint Bonaventure University, Medellin Branch, back in the month of August 2010, who have the tendency to spend their free time in the Virtual Social Networks and then make an analysis of this issue, from the Bioethical viewpoint.